101 Dalmatians - Disney, Walt, 1901-1966; Peet, Bill; Geronimi, Clyde; Luske, Hamilton S.; Reitherman, Wolfgang, 1909-1985; Davis, M., (Marc); Taylor, Rod, 1930-2015; Gerson, Betty Lou, 1914-1999; Bauer, Cat; Daniels, Lisa; Wright, Ben, 1915-1989; Worlock, Frederic, 1886-1973; et al. (Burbank, CA : Walt Disney Home Entertainment : Distributed by Walt Disney Studios Home Entertainment, 2015)
Pongo and Perdita have a litter of 15 dalmatian puppies. Cruella De Vil takes a fancy to the puppies and tries to buy them from their human owners, Roger and Anita. Cruella wants these puppies, as well as more puppies, to make herself a dalmatian skin coat.
Children/Family.
Based on the book "The one hundred and one dalmatians" by Dodie Smith.
Originally produced as a motion picture in 1961.
Special features: All-new digital restoration with enhanced picture and sound; all-new virtual dalmatians game; All-new "Cruella De Vil" music video; deleted songs; Cruella De Vil: drawn to be bad.
Editors, Roy M. Brewer Jr., Donald Halliday ; music, George Bruns ; production designer, Ken Anderson.
Voices: Rod Taylor, Betty Lou Gerson, Cate Bauer, Lisa Daniels, Ben Wright, Fred Worlock, Lisa Davis, Martha Wentworth, J. Pat O'Malley, Tudor Owen.
Keywords: Dalmatian dog -- Juvenile films; De Vil, Cruella (Fictitious character) -- Juvenile films; Dogs -- Juvenile films; Dalmatian dog -- Drama; Dogs -- Drama; De Vil, Cruella (Fictitious character) -- Drama; Children's films; Animated films; Feature films